New record of the genus Baseprocessa (Hemiptera: Cicadellidae: Coelidiinae) from India with description of a new species - Meshram, Naresh M.; Ramaiah, Mogili; Shashank, P R; Stuti (Zootaxa, 2021)
The coelidiinae leafhopper genus Baseprocessa Fan & Li is newly recorded from India based on the description of B. patkaensis Meshram sp. nov. and a proposed new combination, B. serratispatulata (Viraktamath & Meshram) comb. nov. Materials are deposited in the National Pusa Collection, Division of Entomology, ICAR-Indian Agricultural Research Institute (IARI), New Delhi, India. Photographic illustrations, checklist and key to species of this genus along with a distribution map are also provided.